Diversity and distribution of the Caddisflies (Insecta: Trichoptera) of Ecuador - Rios-Touma, B (2017)
This work was supported by Minnesota Agricultural Experiment Station projects MIN-17-017 and 17-029. ERG was funded through the Walter H. Judd Fellowship, University of Minnesota, and a doctoral fellowship from Cienciactiva, Consejo Nacional de Ciencia, Tecnología, e Innovación Tecnológica Peru (contract 277-2015-FONDECYT). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.